Cholera toxin enhances Na + absorption across MCF10A human mammary epithelia - Wang, Qian; Schultz, Bruce D. (American Journal of Physiology: Cell Physiology, 2014)
Cellular mechanisms to account for the low Na + concentration in human milk are poorly defined. MCF10A cells, which were derived from human mammary epithelium and grown on permeable supports, exhibit amiloride- and benzamil-sensitive short-circuit current ( I sc ; a sensitive indicator of net ion transport), suggesting activity of the epithelial Na + channel ENaC. When cultured in the presence of cholera toxin (Ctx), MCF10A cells exhibit greater amiloride-sensitive I sc at all time points tested (2 h to 7 days), an effect that is not reduced with Ctx washout for 12 h. Amiloride-sensitive I sc remains elevated by Ctx in the presence of inhibitors for PKA (H-89, R p -cAMP), PI3K (LY294002), and protein trafficking (brefeldin A). Additionally, the Ctx B subunit, alone, does not replicate these effects. RT-PCR and Western blot analyses indicate no significant increase in either the mRNA or protein expression for α-, β-, or, γ-ENaC subunits. Ctx increases the abundance of both β- and γ-ENaC in the apical membrane. Additionally, Ctx increases both phosphorylated and nonphosphorylated Nedd4-2 expression. These results demonstrate that human mammary epithelia express ENaC, which can account for the low Na + concentration in milk. Importantly, the results suggest that Ctx increases the expression but reduces the activity of the E3 ubiquitin ligase Nedd4-2, which would tend to reduce the ENaC retrieval and increase steady-state membrane residency. The results reveal a novel mechanism in human mammary gland epithelia by which Ctx regulates ENaC-mediated Na + transport, which may have inferences for epithelial ion transport regulation in other tissues throughout the body.